2016
DOI: 10.2147/opth.s105695
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of the vital dye Acid Violet-17 on retinal pigment epithelial cells

Abstract: PurposeTo examine the viability and differentiation of retinal pigment epithelial (RPE) cells after exposure to the vital dye Acid Violet-17 (AV-17).MethodsBovine RPE cells were incubated with AV-17 (0.0625–0.5 mg/mL) for 30 seconds or 5 minutes. Viability was determined by live/dead staining, cleaved CASP3 immunostainings, and MTT test. Actin cytoskeleton was visualized by Alexa 488-phalloidin. Immunocytochemistry was performed to determine the levels of ZO-1, CTNNB1, and KRT19.ResultsExposure to AV-17 at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…AV at low concentrations (0.0125%) in the dark was found not to lead to damage of RPE cells isolated from bovine retina; this was, however, different when the concentration was increased to 0.025% (still below a clinically useful concentration). 48 Penha et al 1 had found similar toxicity levels as ours, while Hurst et al 26 found lower values. A recent survey of the literature by Gerding 3 shows that toxic effects of AV are found at concentrations well below those that were used clinically.…”
Section: Discussionsupporting
confidence: 79%
“…AV at low concentrations (0.0125%) in the dark was found not to lead to damage of RPE cells isolated from bovine retina; this was, however, different when the concentration was increased to 0.025% (still below a clinically useful concentration). 48 Penha et al 1 had found similar toxicity levels as ours, while Hurst et al 26 found lower values. A recent survey of the literature by Gerding 3 shows that toxic effects of AV are found at concentrations well below those that were used clinically.…”
Section: Discussionsupporting
confidence: 79%
“… 26 Consistently, ARPE-19 cells have been largely used to study retinal cytotoxicity and the biocompatibility of vital dyes. 27 31 Finally, the reliability of the results obtained using ARPE-19 cells has been supported by several previous studies evaluating the retinal cytotoxicity/biocompatibility of various intraocular medical devices. For example, comparable results have been documented when retinal ganglion cells and ARPE-19 cells have been used to assess cell viability after exposure to silicone oil (SO), 32 as well as ARPE-19 cell and human retina ex vivo culture model to assess cell viability following exposure to non-cytotoxic PFCL samples.…”
Section: Discussionsupporting
confidence: 54%
“…Preclinical evaluation suggested lack of toxicity at concentrations up to 0.125 mg/ml, 119,120 and some concern for phototoxicity. 92 Ala Medics introduced Ala Purple to the market at a concentration of 1.5 mg/ml.…”
Section: Investigational Dyesmentioning
confidence: 99%